2015
DOI: 10.5505/kjms.2015.32657
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Preoperative Red Cell Distribution Width and Early Postoperative Mortality in Patients with Gastric Cancer

Abstract: AIM: In our study we aimed to investigate whether the preoperative red cell distribution width measurement can predict the early postoperative mortality within the fi rst 30 days in patients with gastric cancer. METHODS: The records of gastric cancer patients operated be GirișMide kanseri (MK) tüm dünyada kanser ölümlerinin en sık ikinci sebebidir. Tanı sırasında hastaların 2/3'ü tümörün rezeksiyonu için uygun değildirler 1 . Tanı ve tedavideki gelişmeler doğrultusunda mide kanserine bağlı ölüm oranları gidere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Therefore, further prospective cohort studies are needed to validate the prognostic value of RDW in GC. Notably, two recently published studies with retrospective design have shown that increased RDW was associated with poor outcomes of among patients with GC . Nevertheless, compared with these studies, the present study has several advantages.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore, further prospective cohort studies are needed to validate the prognostic value of RDW in GC. Notably, two recently published studies with retrospective design have shown that increased RDW was associated with poor outcomes of among patients with GC . Nevertheless, compared with these studies, the present study has several advantages.…”
Section: Discussionmentioning
confidence: 89%
“…However, increasing studies showed that RDW is a valuable index for estimating the disease activity/severity or prognosis of many nonhematology diseases, such as cardiovascular diseases, autoimmune diseases, liver diseases, and cancers . Nevertheless, reports concerning the association between RDW and GC are limited …”
Section: Introductionmentioning
confidence: 99%